Identity and stereotypes - Vuković, Ana (Sociološki pregled, 2025)
The paper discusses the conceptual connection between identity and stereotypes. The first part of the paper includes theoretical determinations of the concept of identity and its main components. In the second part, stereotypes about Serbian identity are stated and the processes in which stereotypes arise and persist throughout history are discussed. It points to strategies of stereotyping, as well as to the dynamic element of identity. In the third part of the paper, a contemporary example of negative self-stereotypes about Serbs is discussed. In conclusion, the author states that identity can be a reflection of stereotypes, but stereotypes alone cannot encompass all elements of identity. Wondering about stereotypes is the only constant, since they are, among other things, a projection of the formation, preservation and (de)construction of identity in the future.
Keywords: culture; social relationship; stereotyping; Serbian identity